Strategy development in tourism destinations : a DEA approach - Fuchs, Matthias (Economics and Business Review, 2004)
The aim of the paper is to introduce an application of Data Envelopment Analysis (DEA) for benchmarking the efficiency of (tourism) service production processes on the level of tourism destinations. After a brief discussion of the latest benchmarking research studies in tourism, an efficiency model for tourism service processes will be developed (Parasuraman 2002). The latter postulates simultaneous consideration of major input resources needed to provide destination experiences (Vuorinen et al. 1998; Fuchs et al. 2002). Comprehensive efficiency measures for a benchmarking group comprising a total of 21 Tyrolean destination units are subsequently obtained by the aid of the Data Envelopment Analysis (Charnes et al. 1978). These empirical findings form the basis for a newly applied strategy development approach for tourism destinations. The paper concludes by discussing major strengths and weaknesses of the presented benchmarking approach and gives recommendations for future research. (original abstract)